Cytotoxic T-cell immunity to influenza. - Mcmichael, A; Gotch, F; Noble, G; Beare, P (1983)
In a study designed to determine whether cytotoxic T lymphocytes contribute to immunity against influenza virus infection, we inoculated 63 volunteers intranasally with live unattenuated influenza A/Munich/1/79 virus. Over the next seven days clinical observations were made, and the amount of virus shed was measured. The protective effects of preinfection serum antibody and of cytotoxic T-cell immunity against influenza A virus were assessed for each participant. All subjects with demonstrable T-cell responses cleared virus effectively. This response was observed in volunteers in all age groups, including those born after 1956, who did not have specific antibody and hence had probably not been exposed to this subtype of influenza A virus before. Cytotoxic T cells show cross-reactivity in their recognition of the different subtypes of influenza A virus, in contrast to the antibody response that is specific for each virus subtype. We conclude that cytotoxic T cells play a part in recovery from influenza virus infection.